Embedded indexing with Word. Part 2 – editing entries and making work easier by using macros. (1st September 2020) - Greulich, Walter
Abstract : In this second article in a series on the under-exploited potential for using Microsoft Word as a tool for embedded indexing, the focus is on editing entries and using macros while the index is being created. This article covers the index entry window, XE fields, separate document templates and exported UI files. It also includes step-by-step instructions for using macros. The first article in the series can be found in The Indexer 38 (2), 207–18.